Community participation in land resource conservation and management in Gombe State, Nigeria - Umar, Saidu Alhassan (2016)
Land degradation in forms of desertification, soil erosion, and pollution has become one of the challenges facing the entire universe. It results in loss of lives, property, and decrease in food crops, climatic changes, extinctions of animals and plants species among others. These problems still constitute a serious challenge in the 21st century. Government’s approach to land resource conservation has been found to be insufficient in addressing the problem, resulting in call for participation of all stakeholders, including NGOs, CBOs, and other local community members, as well as the use of integrated and multi-dimensional approach to the problems of land degradation, yet not much success was recorded. This study attempts to identify the extent of community participation and factors influencing the participation in land resource conservation and management in the local government areas of Gombe State, Nigeria. Survey research method was employed in collecting data from 240 adults (aged 20-above) respondents of both sexes, scattered over 3 local Governments. To augment the short coming of quantitative research, 6 FGD sessions and 6 in-depth interviews were also conducted among the adult members of the communities, community leaders, and forestry officials. The greater part of the data was collected through Multi- Stage Cluster Sampling from 240 respondents, and the data analyzed, using SPSS to determine the relationship between participation and characteristics of individual respondents. Similarly, qualitative findings from the in-depth interviews and the FGD were used in complementing the quantitative data. The result of the findings revealed a very low level of community participation (especially women) in conservation and a continuous dominance of government limiting conservation and management project. Factors such as poverty, inadequate conservation facilities, partisan politics, and lack of motivations are found to be the main influence, hindering participation in land resource conservation and management in the area of study. Thus, only when the poverty level is reduced among the population; education and employment opportunities are improved; people own the project; and only when government is committed to provide adequate conservation facilities and subsidies on other alternative energy sources, among others, would participation in land resource conservation and management increase among the local community.